1988
DOI: 10.1116/1.575679
|View full text |Cite
|
Sign up to set email alerts
|

Helium cryopumping for fusion applications

Abstract: Large quantities of helium and hydrogen isotopes will be exhausted continuously from fusion power reactors. This paper summarizes two development programs undertaken to address vacuum pumping for this application: (i) A continuous duty cryopump for pumping helium and/or hydrogen species using charcoal sorbent and (ii) a cryopump configuration with an alternative shielding arrangement using charcoal sorbent or argon spray. A test program evaluated automatic pumping of helium, helium pumping by charcoal cryosorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies of ITER cryopump regeneration have found three regeneration temperature regimes: 90 K releases all hydrogen isotopes and helium, 300 K releases all other gases except water, and 475 K releases water [Hauer 2007]. Helium pumping with cryopanels requires special techniques have been developed [Sedgley 1988]. The regeneration system for a steady state facility is more challenging than for a low-duty factor facility like ITER, but should be addressed by neutron sources before a hybrid is built.…”
Section: Expansion Tanks and Vacuum Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of ITER cryopump regeneration have found three regeneration temperature regimes: 90 K releases all hydrogen isotopes and helium, 300 K releases all other gases except water, and 475 K releases water [Hauer 2007]. Helium pumping with cryopanels requires special techniques have been developed [Sedgley 1988]. The regeneration system for a steady state facility is more challenging than for a low-duty factor facility like ITER, but should be addressed by neutron sources before a hybrid is built.…”
Section: Expansion Tanks and Vacuum Systemmentioning
confidence: 99%
“…Pump the gas in the end tank. All are readily pumped by cryosurfaces, with one exception: Helium is harder to cryopump, but can be pumped with surfaces below 4.6 K, or by spraying Argon gas onto a cryosurface to weakly bond to helium, or by coating the cryosurface with activated carbon [Sedgley 1988, Dremel 2009]. …”
Section: Sustainment Of a Warm Plasmamentioning
confidence: 99%